The effect of various disturbances on the seeds on the content of chlorophyll a, chlorophyll b, carotenoids, and biomass of cayenne pepper Seedlings - Rupiasih, Ni Nyoman; Gita Hari Yanti, Ni Kadek; Sumadiyasa, Made; Manuaba, I.B.S. (BULETIN FISIKA, 2018)
Study on the effect of various disturbances on the cayenne pepper seeds (Capsicum Frutescens L.) to the content of chlorophyll a, chlorophyll b, carotenoids, and biomass of the plants in the germination period have been done. The disturbances given include UV-C irradiation for 1 hour (S1), microgravity for 12 hours (S2), for 24 hours (S3), and for 48 hours (S4), as well as combined disturbances that are UV-C irradiation for 1 hour followed by microgravity for 12 hours (S5), for 24 hours (S6), and for 48 hours (S7). As comparison, it has been used seeds without treatment called control (S0). The microgravity environment was created using a 2-D clinostat with a rotational speed of 2.7 rpm (1.2 x 10 -4 g). All samples were grown in normal gravity (1 g) environment. Observations were made during the vegetative phase until the plant was 40 days old. Measurements of chlorophyll a, chlorophyll b, carotenoids, and biomass were performed at the plants were 10, 20, and 40 days old. The results showed that disturbances which given on the seeds gave positive effects on the content of chlorophyll a, chlorophyll b, carotenoids, and biomass of the plants. The impacts depend on the duration of the disturbances given.